DEVELOPMENT OF WEBAPPS-BASED E-LEARNING AT SMK MIFTAHUL ANWAR MENES - Mokh Sidqi Fahmi; Didik Aribowo; Irwanto Irwanto (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2023)
Limitations when teaching and learning in the classroom are sometimes many things that hinder teachers from all learning materials to students. This is a case topic for teachers who want to discuss in detail. This difficulty was complained by teachers and students at Miftahul Anwar Menes Vocational High School, sometimes material that needed explanation in class actually had to be explained in a significant amount of time. The method used was Research and Development (R and D) using the example of waterfall development, research and analysis of the required needs. To develop this online learning implementation design product, it uses several stages: 1) Needs Analysis 2) Design 3) Implementation 4) System testing. teachers students) then the final output is declared feasible using the output of the teacher's score the Category 53 Percentage Criteria table is in the interval X more than 42 while the students' Category Criteria Percentage table is 40.8. user ratings are in the interval X 39 which is in the "Very Eligible" category.